2022
DOI: 10.1038/s41598-022-16972-z
|View full text |Cite
|
Sign up to set email alerts
|

LINC00839 promotes malignancy of liver cancer via binding FMNL2 under hypoxia

Abstract: Liver cancer is one of the most common malignant tumors in the world and metastasis is the leading cause of death associated with liver cancer. Hypoxia is a common feature of solid tumors and enhances malignant character of cancer cells. However, the exact mechanisms involved in hypoxia-driven liver cancer progression and metastasis have not been well clarified so far. The aim of this study was to investigate the contribution of long non-coding RNA (lncRNA) in hypoxia promoting liver cancer progression. We scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…The increased LINC00839 in liver cancer cell lines, combined with its pivotal oncogenic role in driving HCC development, has been well documented in vitro [36,37]. Xie et al [37] unveiled LINC00839 as a novel hypoxia-responsive long non-coding RNA in liver cancer. Under hypoxic conditions, the overexpression of LINC00839 significantly fueled liver cancer cell proliferation, migration, and invasion.…”
Section: Liver Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…The increased LINC00839 in liver cancer cell lines, combined with its pivotal oncogenic role in driving HCC development, has been well documented in vitro [36,37]. Xie et al [37] unveiled LINC00839 as a novel hypoxia-responsive long non-coding RNA in liver cancer. Under hypoxic conditions, the overexpression of LINC00839 significantly fueled liver cancer cell proliferation, migration, and invasion.…”
Section: Liver Cancermentioning
confidence: 99%
“…Similarly, another study conducted by Zhou et al 36 also found that LINC00839 promoted the malignant phenotype of HCC cells. Mechanistically ( Figure 4 ), LINC00839 promotes liver cancer progression by interacting with multiple proteins primarily linked to metabolism and RNA transport, and further upregulates FMNL2 expression under hypoxic conditions 37 . And LINC00839 can also function as a sponge for miR-144-3p, leading to increased WTAP expression levels 36 .…”
Section: Cancerous Diseasesmentioning
confidence: 99%
See 3 more Smart Citations